2019
DOI: 10.12659/msm.915312
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Secondary Vertebral Compression Fracture After Percutaneous Vertebroplasty or Kyphoplasty: A Retrospective Study of 650 Patients

Abstract: BackgroundIn this study, we aimed to investigate the risk factors contributing to secondary vertebral compression fractures (SVCF) in patients undergoing percutaneous vertebroplasty (PVP) or kyphoplasty (PKP) due to osteoporotic vertebral compression fracture (OVCF).Material/MethodsBetween January 2010 and December 2017, 650 patients with regular follow-up were identified and retrospectively analyzed in this study. Of these patients, 410 patients underwent PVP and 240 patients underwent PKP surgery. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 30 publications
6
27
1
Order By: Relevance
“…The resultant spinal sagittal decompensation, will lead to persistent lower back pain. 13 Consistent with our findings, a previous study also suggested an association between thoracolumbar fascia injury and postoperative residual lower back pain after PV. 8 However, unlike the previous study which found that patients with thoracolumbar fascia injury benefitted from PV in terms of pain VAS scores, 8 this present study found thoracolumbar fascia injury was a high-risk factor for poor pain relief after PV.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The resultant spinal sagittal decompensation, will lead to persistent lower back pain. 13 Consistent with our findings, a previous study also suggested an association between thoracolumbar fascia injury and postoperative residual lower back pain after PV. 8 However, unlike the previous study which found that patients with thoracolumbar fascia injury benefitted from PV in terms of pain VAS scores, 8 this present study found thoracolumbar fascia injury was a high-risk factor for poor pain relief after PV.…”
Section: Discussionsupporting
confidence: 93%
“…12 Our findings that low BMD was a risk factor for pain is not surprising since previous studies have confirmed that osteoporosis is a risk factor for recurrent vertebral fractures after PV. 2,10,13 In addition, due to the collapse of multiple vertebral bodies, patients with osteoporosis are prone to kyphosis and secondary sagittal imbalances. 2,12 In these patients, nonphysiological compensation can easily lead to back muscle strain and intermittent lower back pain.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the risk factors for SVCF, we analyzed clinical and radiographical parameters including gender, age, BMI, number of primary fractures, primary treatment (PVP/PKP or conservative treatment), non-spinal fracture history, primary fracture at the TL junction, steroid use, bisphosphonate therapy, and HU value of L1. Elderly postmenopausal women are considered at increased risk of refracture, and previous studies showed that old age was independently associated with incidence of refracture, while our study reported that there was no significant difference in terms of age and gender (14). It is commonly thought that obesity leads to higher lumbar spine load, however, BMI did not reach significance in our study.…”
Section: Discussioncontrasting
confidence: 89%
“…10.4% for men and 6.7%~19.3% for women. Therefore, age and bone mass loss are high-risk factors for fracture [5]. Although osteoporosis is one of the important risk factors of vertebral compression fractures, not all vertebral compression fractures have obvious osteoporosis [6].…”
Section: Introductionmentioning
confidence: 99%